PENGALAMAN KOMUNIKASI ANTARA MAHASISWA RANTAU DENGAN ORANG TUA DALAM MEMOTIVASI PENYUSUNAN TUGAS AKHIR - U Simanullang, Friska; Hasfi, Nurul; Naryoso, Agus (Interaksi Online, 2024)
The phenomenon of students pursuing higher education in Indonesia often involves additional challenges when working on their final thesis, particularly due to the distance from their families. This distance frequently leads to complex academic pressures and may result in study delays as well as tragic incidents involving final-year students. Long-distance communication through media becomes crucial in maintaining relationships, providing emotional support, and motivating students amid the limitations of distance and time. This study aims to explore how the communication experiences between students living away from home and their parents influence the motivation for completing their final thesis. The theory applied is the Family Communication Patterns Theory by Ascan F. Koerner and Mary Anne Fitzpatrick, using a phenomenological approach and data collected through in-depth interviews with four student informants. The results of the study indicate that long-distance family communication plays a key role in supporting the thesis-writing process. This communication serves as a medium for maintaining emotional connections, offering support, and providing motivation, despite facing various challenges such as time differences, busy schedules, and technological obstacles like unstable internet connections and limited access to communication devices. The study also found that strong conversational orientation within families creates a supportive environment for students to share their academic progress and challenges, even though parents may not fully understand the specific details of the final thesis. Parental support, both emotional and financial, helps students feel supported throughout the academic process. Open communication between students and parents is also crucial, although some students prefer to seek advice from friends or siblings rather than their parents on specific issues related to their thesis.